Research Review: Recommendations for reporting on treatment trials for child and adolescent anxiety disorders – an international consensus statement. (19th July 2020) - Creswell, Cathy; Nauta, Maaike H.; Hudson, Jennifer L.; March, Sonja; Reardon, Tessa; Arendt, Kristian; Bodden, Denise; Cobham, Vanessa E.; Donovan, Caroline; Halldorsson, Brynjar; In‐Albon, Tina; Ishikawa, Shin‐ichi; et al.
Abstract : Background: Anxiety disorders in children and young people are common and bring significant personal and societal costs. Over the last two decades, there has been a substantial increase in research evaluating psychological and pharmacological treatments for anxiety disorders in children and young people and exciting and novel research has continued as the field strives to improve efficacy and effectiveness, and accessibility of interventions. This increase in research brings potential to draw together data across studies to compare treatment approaches and advance understanding of what works, how, and for whom. There are challenges to these efforts due largely to variation in studies' outcome measures and variation in the way study characteristics are reported, making it difficult to compare and/or combine studies, and this is likely to lead to faulty conclusions. Studies particularly vary in their reliance on child, parent, and/or assessor‐based ratings across a range of outcomes, including remission of anxiety diagnosis, symptom reduction, and other domains of functioning (e.g., family relationships, peer relationships). Methods: To address these challenges, we convened a series of international activities that brought together the views of key stakeholders (i.e., researchers, mental health professionals, young people, parents/caregivers) to develop recommendations for outcome measurement to be used in treatment trials for anxiety disorders in children and young people. Results and Conclusions: This article reports the results of these activities and offers recommendations for selection and reporting of outcome measures to (a) guide future research and (b) improve communication of what has been measured and reported. We offer these recommendations to promote international consistency in trial reporting and to enable the field to take full advantage of the great opportunities that come from data sharing going forward.